Penerapan Metode Simple Additive Weighting (SAW) dan SWARA dalam Pendukung Keputusan Pemilihan Penerimaan Karyawan Apoteker - Salmon, Salmon; Arfyanti, Ita (Building of Informatics, Technology and Science (BITS), 2022)
Drugs are the most important needs in alleviating and overcoming complaints of illness suffered by patients, a patient will certainly go to the nearest drug store or pharmacy to ask for advice in drug selection to a pharmacist, as a pharmacy or drug store Of course, it is very dangerous to choose a pharmacist without proper knowledge and insight into medicines. Failure to choose a pharmacist will result in losses to the company or pharmacy as well as patient safety, so an expert understanding is needed to determine the standards of a pharmacist to be trusted, selecting employees using a decision support system is the right step to reduce the risk that will occur. in the future. The decision support system in this study uses the SWARA method in determining the weight of the criteria based on expert opinion and the Simple Additive weigh (SAW) method as a ranking method based on the highest value. The results of this study selected alternative A4 on behalf of Tika which has a value of 95% as the alternative that most meets the standards